2020
DOI: 10.1186/s12889-020-8244-5
|View full text |Cite
|
Sign up to set email alerts
|

The youth concussion awareness network (You-CAN) - a school-based peer-led intervention to improve concussion reporting and social support: the protocol for a cluster randomized trial

Abstract: Background: Concussion prevalence is increasing in the pediatric population, and is a matter of public health concern. Concussion symptoms can be physical, cognitive, emotional and behavioural, and last longer in high school aged youth than adults. Concussions are underreported in youth due to their lack of knowledge, social environment, perceived outcomes of reporting, norms, and self-efficacy. The Youth Concussion Awareness Network (You-CAN) is a school-based peer-led program designed to increase high school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Similarly, studies examining knowledge outcomes following peer-led education in athletic contexts to improve reporting of concussion or understanding of concussion effects [ 33 ] have shown that athletes demonstrate gains in both knowledge and attitudes around concussion reporting [ 34 ]. Although one study is underway examining peer-support during recovery for high school students with concussion [ 35 ], research into peer-mentoring as an intervention approach for management of concussion has not yet been adequately investigated, and no digital solutions exist to meet needs of this population.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies examining knowledge outcomes following peer-led education in athletic contexts to improve reporting of concussion or understanding of concussion effects [ 33 ] have shown that athletes demonstrate gains in both knowledge and attitudes around concussion reporting [ 34 ]. Although one study is underway examining peer-support during recovery for high school students with concussion [ 35 ], research into peer-mentoring as an intervention approach for management of concussion has not yet been adequately investigated, and no digital solutions exist to meet needs of this population.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the utilisation of a peer-mediated approach to concussion education has shown promise by improving concussion knowledge, concussion attitudes, reporting intention and facilitating attitudinal changes that support peer-recognition among student-athletes. 39,40 Regardless of the approach, identifying relevant role models for the target population appears to be an integral step in facilitating players’ perceptions of the session's acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…First, there is a significant number of youth concussions that go unreported, especially in young athletes dealing with sport-related concussions. 101 103 Second, children and youth are at a critical period of brain maturation, in which neurologic injury can have much larger, lasting impacts than those experiencing a concussion in adulthood. 104 Therefore, even though older children are more likely to experience persistent symptoms, infants and young children are still vulnerable to severe impacts of concussion.…”
Section: Discussionmentioning
confidence: 99%